1997
DOI: 10.1016/s0042-6989(96)00225-8
|View full text |Cite
|
Sign up to set email alerts
|

Visual search of expansion and contraction

Abstract: The perception of expansion/contraction in human subjects was examined with a visual search paradigm. When searching for a target defined by two-dimensional expansion among distractors defined by two-dimensional contraction, the time needed to find the target did not vary as the number of distractors was increased. However, for a target defined by two-dimensional contraction among distractors defined by two-dimensional expansion, the search time increased as a function of the number of distractors in the displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 41 publications
6
53
2
Order By: Relevance
“…Concordant with these theoretical considerations, several behavioral studies reported that the perception of auditory and visual looming and receding signals differs despite identical overall stimulus energy (auditory modality: Gray, 2011;Hall and Moore, 2003;Maier and Ghazanfar, 2007;Schlauch et al, 2001;visual modality: Franconeri and Simons, 2003;Schiff et al, 1962;Takeuchi, 1997). The only discrepancy between those signals is their temporal profile: looming signals increase in amplitude or size over time whereas for receding signals the temporal pattern is reversed.…”
Section: Introductionmentioning
confidence: 77%
“…Concordant with these theoretical considerations, several behavioral studies reported that the perception of auditory and visual looming and receding signals differs despite identical overall stimulus energy (auditory modality: Gray, 2011;Hall and Moore, 2003;Maier and Ghazanfar, 2007;Schlauch et al, 2001;visual modality: Franconeri and Simons, 2003;Schiff et al, 1962;Takeuchi, 1997). The only discrepancy between those signals is their temporal profile: looming signals increase in amplitude or size over time whereas for receding signals the temporal pattern is reversed.…”
Section: Introductionmentioning
confidence: 77%
“…There is little previous data on search within an optic flow background. Two studies examined search for an expanding target amid contracting or deforming distractors and vice versa (Braddick & Holliday, 1991;Takeuchi, 1997), but in these experiments each local item expanded or contracted. This is not equivalent to the global expansion pattern generated by observer motion.…”
Section: Discussionmentioning
confidence: 99%
“…The whole stimulus display with fixation cross was initially presented statically for 1,000 msec to ensure fixation. Then, the ball and the shadow moved and disappeared 200, 400, 600, 800, or 1,000 msec later (corresponding to the target's travel distances studies have reported that the human cognitive system has anisotropic sensitivity to approaching or receding motion that is defined by expanding or contracting motion (Shirai & Yamaguchi, 2004;Takeuchi, 1997) and by a cast shadow's motion (Imura, Shirai, Tomonaga, Yamaguchi, & Yagi, 2008). They showed that approaching motion is easier to detect than receding motion.…”
Section: Methodsmentioning
confidence: 99%